2009
DOI: 10.1001/archgenpsychiatry.2009.50
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder and Hypothalamic-Pituitary-Adrenal Axis Activity

Abstract: This large cohort study shows significant, although modest, associations between MDD and specific hypothalamic-pituitary-adrenal axis indicators. Because a higher cortisol awakening response was observed among both subjects with current MDD and subjects with remitted MDD, this may be indicative of an increased biological vulnerability for depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
446
10
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(504 citation statements)
references
References 63 publications
29
446
10
12
Order By: Relevance
“…The direction of these relationships is somewhat in keeping with previous research. For example, greater early morning peak levels have been associated with greater depressive symp- toms [20]; and while lower evening cortisol levels are usually associated with fewer depressive symptoms [35], there is evidence that evening levels are indeed lower in individuals reporting burnout [36]. Baseline levels of pro-MMP2 were also increased in patients whose ulcers remained unhealed.…”
Section: Discussionmentioning
confidence: 99%
“…The direction of these relationships is somewhat in keeping with previous research. For example, greater early morning peak levels have been associated with greater depressive symp- toms [20]; and while lower evening cortisol levels are usually associated with fewer depressive symptoms [35], there is evidence that evening levels are indeed lower in individuals reporting burnout [36]. Baseline levels of pro-MMP2 were also increased in patients whose ulcers remained unhealed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one study reported no difference in the pattern of the diurnal profile between depressed patients and controls (McClure, 1966). With regard to the CAR, participants who were currently or previously depressed ( [Bhagwager et al, 2005] and [Vreeburg et al, 2009a]) or had higher depressive symptoms (Pruessner et al, 2003b) exhibited a higher CAR. In contrast, one study showed a blunted CAR in depressed participants (Stetler and Miller, 2005).…”
Section: Depression Anxiety Social Support and Cortisolmentioning
confidence: 99%
“…For example, depressed participants with co-morbid anxiety had a higher CAR compared to those with depression alone (Vreeburg et al, 2009a), suggesting that anxiety may exacerbate the effects of depression on diurnal cortisol. There is also evidence that anxiety is independently associated with diurnal cortisol; individuals with high levels of anxiety showed a different pattern of decline across the day compared to those with lower levels of anxiety (Vedhara et al, 2003).…”
Section: Depression Anxiety Social Support and Cortisolmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with previous research. Previous studies reported differences between GAD or MDD compared to healthy controls for cortisol (Bhagwagar et al., 2005; Hek et al., 2013; Hinkelmann et al., 2012; Mantella et al., 2008; Phillips et al., 2011; Steudte et al., 2011; Ulrike, Reinhold, & Dirk, 2013; Vreeburg et al., 2009; Wei et al., 2015) but the exact nature of these differences was mixed and some studies did not find such differences (Burke, Davis, Otte, & Mohr, 2005; see also the meta‐analysis by Vythilingam et al., 2004). The heterogeneity of prior studies can be attributed to methodological differences in data collection (e.g.…”
Section: Discussionmentioning
confidence: 99%